Clinical Value of Three-Dimensional Transvaginal Ultrasound in Diagnosis of Endometrial Receptivity and Ovarian Function in Patients with Infertility. (11th May 2022) - Wu, Jingjing; Zhu, Xiangming; He, Junjun; Ye, Caihong; Pang, Bo; Zhao, Tianying; Bao, Tingting
Abstract : Objective. A case-control study was conducted to explore the clinical value of three-dimensional transvaginal ultrasound in the diagnosis of endometrial receptivity (ER) and ovarian function in patients with infertility. Methods. A total of 308 infertile women treated in our hospital from March 2020 to June 2021 were enrolled as the observation group, and another 300 women of childbearing age who underwent physical examination in the same period were enrolled as the control group. The clinical value of three-dimensional transvaginal ultrasound in ER in patients with infertility was analyzed by comparing the classification of endometrial and subendometrial blood perfusion, endometrial AUC value and Pi value, and subendometrial AUC value and Pi value. According to the number of oocytes obtained, the patients were assigned into the normal response group (182 cases, ≥5 oocytes) and the low response group (126 cases, <5 oocytes). The levels of some hormones, such as follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), and FSH/LH, were measured. Transvaginal ultrasonography was performed to detect ovarian volume (OV), antral follicle count (AFC), and peak flow rate of the ovarian interstitial artery (PSV). The peak of end-diastolic flow velocity (EDV) and other indexes were analyzed. The correlation between FSH level, FSH/LH, and ultrasound indexes was analyzed, and the ROC curve was established to analyze the value of transvaginal Doppler ultrasound in evaluating ovarian reserve function and predicting ovulation. Results. There were significant differences in late proliferation type I and type III, ovulatory type II and type III (P < 0.05 ). There exhibited no significant difference in late proliferation type II, ovulation stage type I, and implantation window stage type I, type II, and type III (P > 0.05 ). Regarding the endometrial AUC and Pi values, the endometrial AUC and Pi values in the observation group were lower compared to the control group during late proliferation and ovulation (P < 0.05 ). There exhibited no significant difference in AUC and Pi (P > 0.05 ). Regarding the subintimal AUC and Pi values, the subintimal AUC and Pi values in the observation group were higher compared to the control group during late proliferation and ovulation (P < 0.05 ). There exhibited no significant difference in AUC and Pi during the implantation window (P > 0.05 ). There exhibited no significant difference in menarche age, age, body mass index, and menstrual cycle between the normal response group and the low response group (P > 0.05 ). The levels of EDV, OV, AFC, and PSV in the normal response group were higher compared to the low response group (P < 0.01 ). Compared with the low response group, the levels of FSH and FSH/LH in the normal response group were lower, but the levels of LH and E2 in the normal response group were higher (P < 0.05 ). The results of correlation analysis of FSH, FSH/LH, and ultrasound parameters between the normal response group and the low response group indicated that FSH was negatively correlated with E2, EDV, OV, AFC, and PSV in 308 infertile women (r = − 0.817, -0.846, -0.707, -0.845, -0.911, P < 0.01 ), but it was positively correlated with FSH/LH (r = 0.714, P < 0.01 ). The ultrasound parameters of ovarian reserve function in the normal response group and the low response group were compared with the indexes that predicted ovulation. The results of ROC curve analysis indicated that the cutoff values of EDV, OV, AFC, and PSV were 4.141, 3.726, 4.106, and 13.944, respectively, the specificity of each index was higher than 90.00%, and the sensitivity was higher than 80.00% except PSV. Conclusion. Transvaginal ultrasound can not only accurately evaluate the ER of infertile women but also directly observe follicular development and monitor ovulation, which is of high value in evaluating ovarian reserve function and predicting ovulation.